Assessing Student’s Perception on Blended Learning Approach as a strategic Initiative in Higher Education - Shokeen, Anjali (International Journal of Psychosocial Rehabilitation, 2020)
The world is undergoing rapid changes with the emergence of Informational Technology. It has become inevitable and necessary because of its positive effects in educational field. Moreover, these days teaching in universities has become more challenging job due to diversity, cultural and personality differences among students. Due to differences in learning styles and variation in preferences of students, teachers have been thinking different ways to make learning more effective and interactive. Blending Learning approach is very helpful in interactive learning where teacher’s role in face-to-face mode is blended with the virtual mode. The present paper discusses the student’s perception on Blended Learning approach. The sample of the study includes 120 students enrolled in various departments at Guru Gobind Singh Indrapratha University. The rating scale was made to know the perception of students towards Blended Learning Approach in terms of ease of use, mode of Teaching and its effectiveness. The study concludes that the student’s perception towards Blended Learning Approach is positive in terms of all three domains of the form. The results show that students have positive attitude towards Blended Learning approach and it is an effective approach for enhancing competencies and skills among students. The results of the study also suggest that Blended Learning should be incorporated in all courses of Higher education institutions to have the desired results.